2007
DOI: 10.1007/s00595-007-3562-0
|View full text |Cite
|
Sign up to set email alerts
|

Ductal Carcinoma In Situ Arising in a Benign Phyllodes Tumor: Report of a Case

Abstract: Malignant epithelial change within a phyllodes tumor (PT) is a rare event. To our knowledge, only six cases of ductal carcinoma in situ arising in a PT have been reported in English. We report a case of PT with an intraductal carcinoma component, which grew rapidly to a huge size in 3 months. Histologically, the stromal element showed mild to moderate cellularity with few mitoses and mild nuclear atypia. The epithelial element consisted of irregularly dilated ducts with a phyllodes structure that had moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…As there is no standard adjuvant treatment strategy for this type of disease, a variety of systemic therapies were applied to the various cases. In total, 6 cases received chemotherapy with various regimens (16,(19)(20)(21)(22)(23), 5 cases received radiotherapy (13,16,18,20), and 4 cases received endocrine therapy, 3 of which received tamoxifen (1,16,21) and 1 received tamoxifen and goserelin (19). Patient outcomes were described in 19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…As there is no standard adjuvant treatment strategy for this type of disease, a variety of systemic therapies were applied to the various cases. In total, 6 cases received chemotherapy with various regimens (16,(19)(20)(21)(22)(23), 5 cases received radiotherapy (13,16,18,20), and 4 cases received endocrine therapy, 3 of which received tamoxifen (1,16,21) and 1 received tamoxifen and goserelin (19). Patient outcomes were described in 19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis for cases of ductal carcinoma in situ within phyllodes tumors is generally favorable, with no deaths yet reported. Axillary lymph node dissection is not part of the standard treatment for phyllodes tumors as lymph node spread is rare, and may thus be restricted to patients suspected of having lymph node involvement by image diagnosis (5,9,16).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant phyllodes tumors are treated like sarcomas and en bloc surgical resection is recommended. Recurrence rates for benign, borderline and malignant phyllodes tumors are %17, %25, %27, respectively (4,5). Malignant transformation of the tumor usually occurs in the stromal part of the tumor but the epithelial component of phyllodes tumors can transform into a malignancy too (6).…”
Section: Introductionmentioning
confidence: 99%
“…Nomura et al (7) reported that mammography revealed a welldefined tumor with a diameter of 3.3 cm, and US revealed a tumor with a regular border and low echogenicity. Yamaguchi et al (8) described the tumor as a mixed cystic and solid mass on US and magnetic resonance imaging. There are no specific clinical or radiologic clues to indicate the presence of in situ carcinoma within a phyllodes tumor (2).…”
Section: Index Termsmentioning
confidence: 99%